Perspectives on Peace Education of Muslim Scholars and Educators in Sulu, Philippines - Salasain, Abdel Ajim M. (Future Science / FSH-PH Publications, 2025)
his research explores the attitudes of Muslim Filipinos in Sulu in the context of how Islamic doctrine supports peace and nonviolence among them. This study addresses a gap in peace education for Min-danao with a specific emphasis on knowing the perceptions of local Islamic scholars and educators of peace-building practice. The meth-odology undertaken in the conduct of this research is a mixed-method approach involving both quantitative and qualitative ap-proaches. A survey questionnaire was administered to 331 students in Teacher Education. Semi-structured interviews were conducted with 59 educators and scholars. Descriptive statistics and content analysis served the purposes of data analysis (Aming-Hayudini et al., 2024). The goal was to find recurring themes and patterns.Key findings reveal that 87% of respondents strongly agree that Islam promotes peace, with the Qur'an and the teachings of Prophet Muhammad emphasizing the sanctity of human life, peaceful conflict resolution, and the avoidance of violence. Specifically, 92 percent of the teaching and academic faculty believe that a peaceful inner heart is a basic requirement for world peace, while 86 percent believe that, in Islam, peace is connected with justice, and 81 percent believe inter-faith dialogue and cooperation are imperative to promote different communities' mutual understanding. The study also identified the significant role of Islamic teachings on justice and the importance of Sharia (Islamic Jurisprudence) in ensuring a just society.The conclusion underscores that Islamic peace education, rooted in the principles of submission to Allah’s will, adherence to Qur’anic guidance, and promoting justice through Sharia, is vital for long-term peace-building in Sulu. Educators and scholars in the region play a critical role in moving forward with these values and supporting peace initiatives consistent with the principles of Islam. This re-search finds that the Islamic peace education approach should be in-cluded in both formal and informal learning systems in Mindanao, especially in Sulu, as a solution to the problems facing the region re-garding conflict and establishing a more peaceful society.